2022
DOI: 10.3390/agriculture12020260
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate and Plant Transpiration of Tomato (Solanum lycopersicum L.) in a Sunken Solar Greenhouse in North China

Abstract: The solar greenhouse is a common protected structure for crop production when ambient temperatures are low. In the North China Plain (NCP) winter temperatures are very low and an improved solar greenhouse with a lowered soil surface (0.5–1.5 m deep), referred to as a sunken solar greenhouse (SSG), is used. A four-season experiment was conducted in a commercial SSG with tomato crops to characterize internal microclimate, sap flow (SF) and crop coefficients. Results show that temperature inside the SSG could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Lead concentration in shoots and roots, as well as total lead concentration, have a direct effect on the efficiency of lead absorption is -19.9%, 89%, and 67.8%, respectively. The indirect influence can be seen in table 19 showing that the influence varies greatly. Light intensity, temperature, relative humidity, leaf area, Concentration of lead in shoot and root, and total lead concentration indirectly affect the efficiency of absorption of lead respectively by 10.2%; -5.3%; 14.3%; -23.6%; 11.5%; 69.2%; 67.8%, but the indirect relationship between leaf area is negative, meaning that narrow leaves have a higher efficiency of absorption of lead compared to other treatments.…”
Section: Relationship Between Microclimate Parameters and Efficiency ...mentioning
confidence: 97%
See 1 more Smart Citation
“…Lead concentration in shoots and roots, as well as total lead concentration, have a direct effect on the efficiency of lead absorption is -19.9%, 89%, and 67.8%, respectively. The indirect influence can be seen in table 19 showing that the influence varies greatly. Light intensity, temperature, relative humidity, leaf area, Concentration of lead in shoot and root, and total lead concentration indirectly affect the efficiency of absorption of lead respectively by 10.2%; -5.3%; 14.3%; -23.6%; 11.5%; 69.2%; 67.8%, but the indirect relationship between leaf area is negative, meaning that narrow leaves have a higher efficiency of absorption of lead compared to other treatments.…”
Section: Relationship Between Microclimate Parameters and Efficiency ...mentioning
confidence: 97%
“…In general, air temperature, relative humidity and light intensity have been known as principal actuators among the various microclimate factors for plant growth and development, especially biomass production [18]. Microclimate is a critical parameter for crop production as it influences the water balance and photosynthesis process in the plants [19].…”
Section: Microclimate Factormentioning
confidence: 99%
“…Increasing the number of roof vents (roof vent area) resulted in a higher overall ventilation rate but weaker air movement at the crop level [85,86]. Yan [87] compared the ventilation performance in CSG with rear slope integral vents, rear slope interval vents, and top end vents (Figure 3a-c). The rear slope vents resulted in a higher daily average wind speed.…”
Section: Factors Influencing Ventilation Rates 231 Vent Size Shape An...mentioning
confidence: 99%
“…Figure 3. Chinese solar greenhouses with top end vents (a), rear slope integral vents (b), and rear slope interval vents (c)[87], and vents on the back wall (d)[89].…”
mentioning
confidence: 99%
“…Several studies have analyzed environmental microclimate conditions to evaluate and optimize crop growth conditions and to improve the energy efficiency of greenhouses. The microclimate and transpiration of tomato plants have been investigated [22] in a sunken solar greenhouse located in North China. The findings revealed that the sunken design of the greenhouse improved the microclimate by lowering temperature fluctuations and increasing relative humidity.…”
Section: Introductionmentioning
confidence: 99%